Practical Aspects of Home and Ambulatory Blood Pressure Monitoring - Peixoto, Aldo J. (Methodist Debakey Cardiovasc J, 2015)
Out-of-office blood pressure (BP) monitoring is becoming increasingly important in the diagnosis and management of hypertension. Home BP and ambulatory BP monitoring (ABPM) are the two forms of monitoring BP in the out-of-office environment. Home BP monitoring is easy to perform, inexpensive, and engages patients in the care of their hypertension. Although ABPM is expensive and not widely available, it remains the gold standard for diagnosing hypertension. Observational studies show that both home BP and ABPM are stronger predictors of hypertension-related outcomes than office BP monitoring. There are no clinical trials showing their superiority over office BP monitoring in guiding the treatment of hypertension, but the consistency of observational data make a compelling case for their preferential use in clinical practice.